2018
DOI: 10.1101/285676
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A genetic link between whole-plant water use efficiency and leaf carbon isotope composition in the C4 grass Setaria

Abstract: Increasing whole plant water use efficiency (yield per transpiration; WUEplant) through plant breeding can benefit the sustainability of agriculture and improve crop yield under drought. To select for WUEplant, an efficient phenotyping method that reports on the genetic contribution of component traits such as transpiration efficiency (TEi; rate of CO2 assimilation per stomatal conductance) must be developed. Leaf carbon stable isotope composition (δ13Cleaf) has been proposed as a high-throughput proxy for TEi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 81 publications
3
4
0
Order By: Relevance
“…4a), observed also in other C 4 species (Henderson et al 1998; Dercon et al 2006; Sharwood et al 2014). A significant difference between NIL B and the recurrent parent in grain δ 13 C was observed only in well-watered conditions, in agreement with findings in the C 4 species Setaria (Ellsworth et al 2018), where differences in δ 13 C were small under water-limited conditions. The authors explain this with lower stomatal conductance leveling differences in transpiration efficiency and hence differences in δ 13 C between genotypes, like it was reported in C 3 species (Adiredjo et al 2014) and maize (Alvarez Prado et al 2018).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…4a), observed also in other C 4 species (Henderson et al 1998; Dercon et al 2006; Sharwood et al 2014). A significant difference between NIL B and the recurrent parent in grain δ 13 C was observed only in well-watered conditions, in agreement with findings in the C 4 species Setaria (Ellsworth et al 2018), where differences in δ 13 C were small under water-limited conditions. The authors explain this with lower stomatal conductance leveling differences in transpiration efficiency and hence differences in δ 13 C between genotypes, like it was reported in C 3 species (Adiredjo et al 2014) and maize (Alvarez Prado et al 2018).…”
Section: Discussionsupporting
confidence: 90%
“…Taken together, the findings in Setaria and our results in maize demonstrate a genetic and physiological association between δ 13 C and WUE in C 4 species, which most probably involves regulation through stomatal conductance. We showed that, in maize, grain δ 13 C is both genetically determined and responsive to drought as it has recently been shown for leaf δ 13 C in Setaria (Ellsworth et al 2018 ). Hence, our results suggest that, in spite of the fact that the underlying mechanisms are still not clear, δ 13 C can be used in maize as a proxy of other variables involved in drought tolerance.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations